Математические модели с функцией контроля для исследования дробно-дифференциальной динамики геомиграционных процессов - Булавацкий, В.М.; Кривонос, Ю.Г. (Проблемы управления и информатики, 2014)
Побудовано дробово-диференціальні математичні моделі з функцією контролю для дослідження динаміки деяких локально-нерівноважних у часі неізотермічних геоміграційних процесів. Моделі базуються на поняттях узагальнених похідних Капуто та Хільфера як похідних дробового порядку від функції по іншій функції. У рамках цих моделей одержано аналітичні розв’язки двох крайових задач геоміграції. The fractional-differential mathematical models with a function of the control for investigation of dynamics of some locally — non-equilibrium in time nonisothermal geomigration processes are constructed. The models base on concepts of generalized Caputo and Hilfer derivatives, as derivatives of the fractional order from a function on other function. Within the framework of these models the analytical solutions of two boundary value problems of geomigration are obtained.